The evolution of the black wildebeest, Connochaetes gnou, and modern largemammal faunas in central Southern Africa - Brink, James Simpson (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Archaeology))--University of Stellenbosch, 2005.